AN ANALYSIS OF FACTORS INFLUENCING LEARNERS’ IN LEARNING LANGUAGE - Franscy; Rezki Puteri Syahrani Nurul Fatimah (Department of English Education, Universitas Panca Sakti Bekasi, 2019)
The aim of this research is to describe the factors influencing learners’ in learning language. This research used qualitative approach. Type of the data in this research is qualitative data that consist by collecting library data, reading, recording and processing library collection materials without need field research. This research presents scientific reasoning arguments from the result of literature review and the researcher' thinking about the problems in learning language. The library materials are discussed critically and deeply in support of discussing the factors influencing learners’ in learning language. Research result shows that there are four important factors in education process that have an influence on the process of teaching and learning language, these factors include curriculum factor, institution factor, teacher factor, teaching factor and students factor. From understanding and analysis the theory indicated that in the process of teaching and learning language as effectively category, not only focus on teacher and students factors, but also other factors have relevance and influence with each other, to achieve the learning purpose. Therefore, understanding the role and function of four factors are very important in creating an effectiveness design of learning language for learners. An understanding the creation of effective learning language process is required in order to obtain synergy and perfect preparation of all the important factors above. So, the process learning language in our educational environment will achieve the expected goals.